Konsep Uzlah menurut Imam Nawawi al-Bantani - Ibrahim Hasan Mauludi (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to analyze the concept of uzlah Imam Nawawi Al-Bantani and its relevance to modern life. This study uses a qualitative approach with a Library study approach. The analysis method used is a descriptive content analysis technique. This study found that the uzlah written by Imam Nawawi Al-Bantani was not a form of self-exile from society and was carried out throughout life, but rather isolated oneself from befriending the bad class of morals to the sholih people to perfect themselves towards akhlakul karimah. Uzlah is also an attempt by modern society to control itself from the influence of negligence in technology. The result of uzlah is not to abandon world affairs, but to be able to live it with discipline, responsibility, and steadfastness in holding the commandments of Allah Almighty. So that Uzlah can be a path taken to complete the life of the world.